Free research for all? How the Unpaywall browser extension is affecting scholarly communication - Hymers, Jessica (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2026)
This commentary reflects on the potential impacts of the technology, Unpaywall, on the systems of scholarly research dissemination. Unpaywall is a technological tool used to increase access and discoverability of Open Access versions of paywalled articles, making materials visible, disrupting current infrastructures, and highlighting existing alternatives. Because of its reliance on the external standard of the Digital Object Identifier, however, it also risks perpetuating the inequalities that already exist in this space. I explore how technologies affect surrounding infrastructures, how these effects are reflected in higher-level systems, and how they can be evaluated for alignment with professional standards and established goals.